Testicular Cancer Treatments and Sexuality: A Narrative Review - Massimiliano Raffo; Angelo Di Naro; Luigi Napolitano; Achille Aveta; Simone Cilio; Savio Domenico Pandolfo; Celeste Manfredi; Chiara Lonati; Nazareno Roberto Suardi (Medicina, 2024)
The incidence of testicular cancer (TC) has been rapidly increasing over the past years. Diagnosis and early treatment have shown good oncological control, guaranteeing the patient different treatment approaches according to histology and tumor stage. Currently, physicians usually prioritize oncological outcomes over sexual outcomes and quality of life, considering as a first aim the overall survival of the patients; however, differently from other neoplasms, quality of life is still strongly affected among TC patients, and sexual outcomes are frequently compromised after each TC treatment. Several studies have suggested that each treatment approach may be associated with sexual dysfunctions, including erectile dysfunction, ejaculatory disorders, fertility issues, and hormonal changes. Since testicular cancer patients are more frequently young men, the subject of this work is substantial and should be analyzed in detail to help specialists in the management of this disease. The aim of the current narrative review is to generally describe every treatment for TC, including surgery, chemotherapy, radiotherapy, and retroperitoneal lymph node dissection, and to establish which sexual dysfunction may be specifically associated with each therapy.